ASAS KEBEBASAN BERKONTRAK DALAM PERJANJIAN KREDIT DAN JAMINAN - Wulandari, Retno (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2022)
Abstract Take it or leave it, that is what happens in the development of contract law, especially for contracts where there is almost no bargaining position, especially for a debtor in a credit and guarantee contract or agreement in the banking world. The increasing rate of growth in consumption of goods and/or services is one indicator that shows the development of national and international trade activities. This condition is also supported by advances in science, telecommunications and information technology (internet) as well as modern modes of transportation that provide freedom of movement for transactions of goods and/or services to cross the boundaries of a country. The rapid exchange of data in the world of information and technology has had a significant impact on business behavior and contractors, such as fast food (fast food) existing business contracts have also been